Cyberbullying Among Islamic University Faculties - Salsabila, Khalishah (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2023)
Cyberbullying in the present is experienced by many students, ranging from elementary school, junior high school, high school, to college. The number of mentally injured students makes this cyberbullying even more dangerous if not addressed. Because there are so many Islamic students who are affected by this problem, we decided to discuss this issue. In this study, we asked if they knew or had experienced some form of cyberbullying as well as for those who had experienced whether or not they reported it. The method we use in writing this journal is quantitative by collecting data through a questionnaire. The study concludes that cyberbullying in Islamic university environments is still widely occurring, where many forms of cyberbullying are online fights, and most of the victims do not report the incident. It was also found females had a higher risk of cyberbullying than males.